2014
DOI: 10.1007/s10103-014-1520-9
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of porcine bone tissue with an ultrashort pulsed laser (USPL) system

Abstract: Ultrashort pulsed lasers (USPLs) represent a new generation of laser systems in the field of biophotonical applications. In terms of a pilot project, the study was carried out to evaluate the ablation parameters of bone tissue regarding the medical use of such a laser technology in dentistry. Specimens from ribs of freshly slaughtered pigs were assembled and irradiated with an USP Nd:YVO4 laser (pulse duration 8 ps at 1,064 nm with repetition rates between 50 and 500 kHz) using eligible average output powers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…The SEM and microscopic images showed that ablation width and depth increases with repetition rate. Previously, it has been shown that the ablation rate can be further increased through increasing the laser pulse energy or scanning speed . We used a fluence of 40 J/cm 2 in this study which is higher than the reported ablation threshold for hard tissue of 1 J/cm 2 by Neev et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SEM and microscopic images showed that ablation width and depth increases with repetition rate. Previously, it has been shown that the ablation rate can be further increased through increasing the laser pulse energy or scanning speed . We used a fluence of 40 J/cm 2 in this study which is higher than the reported ablation threshold for hard tissue of 1 J/cm 2 by Neev et al .…”
Section: Resultsmentioning
confidence: 99%
“…This illustrates the importance of using high repetition rates for faster removal of bone. It has been demonstrated that ablation rates of bone samples can be increased by increasing pulse energy and also by increasing the laser repetition rate . In addition, it has been shown that the threshold for ablation decreases as repetition rate is increased .…”
Section: Introductionmentioning
confidence: 99%
“…Mechanic tools allow an ablation rate over 1 mm 3 /s, so to be in a competitive position, a similar ablation rate value with lasers is desirable. The importance of this can be seen in the literature, with plenty of publications about the ablation rate of bone with a wide variety of laser systems, with wavelengths ranging from ultraviolet to mid infrared, and any kind of pulse duration: Continuous wave, microseconds [5,6,7], nanoseconds (ns) [9], picoseconds (ps) [8,10], and femtoseconds [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Irradiation of hard tissues with these lasers shows high ablation rates and low thermal damage, but present some problems like sub-superficial cracking, or tissue necrosis at some degree [14,15]. On the other hand, ultrafast laser sources, although with ablation rates lower than the obtained with mechanical tools, produce an ablation with almost none of the thermal effects [10,11,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to well established mechanical instruments for cutting bone, laserosteotomes provide several important benefits like functional cuts, minimal invasiveness, non-contact interaction, and accelerated healing [1][2][3][4][5][6][7][8][9][10]. At the same time, they still suffer from a lack of feedback on the type and properties of the tissue being cut; as a result, critical structures of the body under the laser line are prone to iatrogenic damage [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%